Reports. - American Psychological Association. Project on Scientific Information Exchange in Psychology; National Science Foundation (U.S.) Office of Science Information Service (Washington Project on Scientific Information Exchange in Psychology, American Psychological Association, 1963)
Irregular
"Reports of work performed under NSF Grant G-18494 from Office of Science Information Service of the National Science Foundation."
Keywords: Communication in psychology; Communication in science; Psychology